2002
DOI: 10.1046/j.1460-9592.2002.t01-1-00856.x
|View full text |Cite
|
Sign up to set email alerts
|

Brugada‐Like Electrocardiographic Pattern Induced by Fever

Abstract: The Brugada syndrome is characterized by a peculiar ST-segment elevation in the right precordial leads and the propensity to develop ventricular arrhythmias. Mutations in a cardiac sodium channel gene have been linked to this syndrome and some experimental data suggest that the dysfunction of the mutated channel can be temperature sensitive. This report describes a patient in whom a typical Brugada ECG pattern developed in relation to fever but could not be reproduced at normal temperature on administration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
1
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(61 citation statements)
references
References 11 publications
5
52
1
3
Order By: Relevance
“…4) Several clinical reports have indicated that a febrile state unmasked the syndrome or exacerbated ST-segment elevation and arrhythmogenesis. [10][11][12][13][14] Our present report supports the temperature-dependent nature of the underlying ion channelopathy of Brugada syndrome. It seems clear that this patient did have Brugada syndrome as indi- cated by a structurally normal heart and positive response to pilsicainide challenge.…”
Section: Discussionsupporting
confidence: 86%
“…4) Several clinical reports have indicated that a febrile state unmasked the syndrome or exacerbated ST-segment elevation and arrhythmogenesis. [10][11][12][13][14] Our present report supports the temperature-dependent nature of the underlying ion channelopathy of Brugada syndrome. It seems clear that this patient did have Brugada syndrome as indi- cated by a structurally normal heart and positive response to pilsicainide challenge.…”
Section: Discussionsupporting
confidence: 86%
“…Cardiac events (syncope or cardiac arrest) occur predominantly in males in the third and fourth decades of life, although presentation with cardiac arrest in neonates or children have been reported (104,777,820). Fever is a predisposing factor for cardiac arrest in the Brugada syndrome (800,818,(821)(822)(823)(824).…”
Section: Causes and Risk Factorsmentioning
confidence: 99%
“…Another known inducing factor is fever. Fever is known to cause ST elevation more prominent in BS and a BS-like ECG pattern in normal subjects (7,9).…”
Section: Discussionmentioning
confidence: 99%